The effects of corrective information about disease epidemics and outbreaks: Evidence from Zika and yellow fever in Brazil - Carey, John Michael; Chi, Victoria; Nyhan, Brendan; Zeitzoff, Thomas; Flynn, Daniel (American Association for the Advancement of Science, 2020)
Disease epidemics and outbreaks often generate conspiracy theories and misperceptions that mislead people about the risks they face and how best to protect themselves. We investigate the effectiveness of interventions aimed at combating false and unsupported information about the Zika epidemic and subsequent yellow fever outbreak in Brazil. Results from a nationally representative survey show that conspiracy theories and other misperceptions about Zika are widely believed. Moreover,results from three preregistered survey experiments suggest that efforts to counter misperceptions about diseases during epidemics and outbreaks may not always be effective. We find that corrective information not only fails to reduce targeted Zika misperceptions but also reduces the accuracy of other beliefs about the disease. In addition,although corrective information about the better-known threat from yellow fever was more effective,none of these corrections affected support for vector control policies or intentions to engage in preventive behavior. Copyright © 2020 The Authors,some rights reserved.
Keywords: Surveys; Control policy; Epidemiology; animal; Brazil; epidemic; human; mosquito vector; pathogenicity; virology; yellow fever; Yellow fever virus; Zika fever; Zika virus; Animals; Brazil; Disease Outbreaks; Epidemics; Humans; Mosquito Vectors; Yellow Fever; Yellow fever virus; Zika Virus; Zika Virus Infection; ODS 3 - Salud y bienestar